PSIKOLOGI PENDIDIKAN DALAM PROSES BELAJAR MENGAJAR - Anny Izzatul Mujahidah (JIPDAS (Jurnal Ilmiah Pendidikan Dasar), 2025)
Educational psychology is a branch of psychology that plays a crucial role in understanding the teaching and learning process. This study aims to examine the role of educational psychology in improving the effectiveness of learning in the school environment. The primary focus is on understanding student characteristics, learning motivation, learning styles, and the relationship between teachers and students that influence learning outcomes. The method used is a literature review with a qualitative-descriptive approach, which examines various relevant literature and theories. The results of the study indicate that applying the principles of educational psychology can help teachers design learning strategies that are more adaptive and responsive to student needs. Thus, understanding the psychological aspects of education is a key factor in creating a conducive and productive learning environment.